Retreatment with peg-interferon and ribavirin in patients with chronic hepatitis C virus genotype 2 or 3 infection with prior relapse. (July 2013) - Lagging, Martin; Rembeck, Karolina; Rauning Buhl, Mads; Christensen, Peer; Dalgard, Olav; Färkkilä, Martti; Hellstrand, Kristoffer; Langeland, Nina; Lindh, Magnus; Westin, Johan; Norkrans, Gunnar
Abstract Objectives. Uncertainty remains regarding the efficacy of retreatment with current standard-of-care peg-interferon (peg-IFN) and ribavirin among patients infected with hepatitis C virus (HCV) genotypes 2 or 3 with relapse after prior therapy. Materials and methods. Seventy-one patients with chronic HCV genotype 2/3 with prior relapse were enrolled in a phase III multicenter study. Patients were retreated with peg-IFNα-2a 180 μg per week and ribavirin 1000/1200 mg daily. Patients having received previous therapy for 24 weeks were retreated for 48 weeks (Group A), whereas patients having received at least 12 weeks but less than 24 weeks of treatment were allocated to either 48 (Group B) or 24 weeks (Group C) on the basis of whether they had achieved rapid virological response (RVR). Results. Sustained virological response (SVR) rates of 53%, 81% and 75% were achieved in groups A, B and C, respectively. Patients with favorable baseline characteristics, e.g., less advanced liver fibrosis, age <40 years, duration of infection <20 years, or BMI < 25 kg/m2, tended to have more favorable outcomes. All patients achieving HCV RNA below 1000 IU/mL day 6 achieved SVR in contrast to none of the patients with detectable HCV RNA at week 12. Conclusions. Retreatment with peg-IFN and ribavirin for 24–48 weeks entails SVR among the majority of HCV genotype 2/3 infected patients with prior relapse. However, in light of the prolonged treatment duration, moderate effect and considerable side effects, deterring therapy until new options are available may be preferential, particularly in patients previously treated for 24 weeks.